Pengembangan Media Pembelajaran Berbasis Augmented Reality Mata Pelajaran Bahasa Sunda untuk Siswa Sekolah Dasar - Rissa Nurmalasari; Ni Ketut Kertiasih; Agus Aan Jiwa Permana (YASIN, 2026)
Sundanese language learning in elementary schools plays an important role in maintaining the continuity of the regional language and script, but students’ interest in and understanding of the material remain relatively low because the learning process tends to be conventional and has not optimally utilized technology. In addition, the development of Augmented Reality (AR)-based learning media that specifically contain material introducing pets and ornamental plants in the Sundanese language and script for elementary school students is still limited. This study aims to design learning media as a means of introducing the Sundanese language and script to elementary school students. This study used the Research and Development (R&D) method with the Multimedia Development Life Cycle (MDLC) model, which includes the stages of conceptualization, design, material collection, development, testing, and distribution. Material validation was carried out by two content experts using the Gregory method with a result of 0.93, which falls into the very high validity category, while the assessment of media aspects by one media expert obtained a score of 93.64% in the very good category. The user test involved four teachers and 20 students in Grades III to VI of elementary school using the System Usability Scale (SUS) questionnaire, with the teachers’ SUS score of 75 categorized as good (Grade C) and the students’ score of 80.25 categorized as good (Grade B). To measure the improvement in learning outcomes, a pretest and posttest were administered to 20 students using 10 question items, and the results of the Paired T-Test analysis showed a sig. (2-tailed) value of 0.01 < 0.05, indicating a significant improvement in learning outcomes after the use of the media. The developed media takes the form of an Android application that can be used offline and functions as an alternative interactive learning tool to support the preservation of the Sundanese language and script.